Analisis Strategi Bisnis Pada Pt. Galleon Cahaya Investama Untuk Meningkatkan Daya Saing Dalam Persaingan Di Pasar - Yakobus Luke (Universitas Tarumanagara, 2019)
This study is to analyze and formulate the best strategy for PT. Galleon Cahaya Investama. This study uses IFE, EFE, SWOT, IE Matrix and QSPM Matrix to obtain the best result for the company. Source of data derived from observations, questionnaires and interviews with the related parties of the company, literature studies and related additional data. The usage of IFE Matrix and EFE Matrix is to analyze the internal and external factors of PT. Galleon Cahaya Investama. Trough these methods, the analysis applied for strength, weaknesses, opportunities and threats. While SWOT analysis will give the wide range of alternative strategies that can be used by PT. Galleon Cahaya Investama. IE Matrix will give us the position of company’s condition. The analysis obtained from the input stage and matching stage would be combined and analyzed through a further process to get the best strategy by using QSPM Matrix. The conclusion of this study is market development strategy because PT. Galleon Cahaya Investama has sufficient strength and must take the advantage of existing opportunities. Furthermore there are so many development and customer needs that must be fulfilled. To excel in such competition, PT. Galleon Cahaya Investama has to use their human resources skill in order to increase customer satisfaction.